2008
DOI: 10.3892/ijmm.21.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human selenoprotein M differentially regulates the concentrations of antioxidants and H2O2, the activity of antioxidant enzymes, and the composition of white blood cells in a transgenic rat

Abstract: Abstract. Selenoprotein is associated with a variety of serious diseases, including infectious diseases, neurodegenerative disorders, cancer and cardiovascular disease. The aim of this study was to produce a new transgenic (Tg) rat expressing human selenoprotein M (SelM) in order to examine the protective function of the antioxidant status in vivo. To achieve this, a new lineage of Tg rats was produced by the microinjection of pCMV/GFP-hSelM constructs into a fertilized rat egg. Several conclusions can be draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
2
31
0
2
Order By: Relevance
“…Therefore, the key point in the prevention and control of AS is inhibiting the excessive apoptosis of vascular endothelial cells induced by oxygen radicals. In the present study, high concentrations of H 2 O 2 led HUVECs to undergo apoptosis, which is consistent with the findings of other studies (23,24). However, the mechanisms of apoptosis are quite complex and are controlled by various pathways and signals (25).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the key point in the prevention and control of AS is inhibiting the excessive apoptosis of vascular endothelial cells induced by oxygen radicals. In the present study, high concentrations of H 2 O 2 led HUVECs to undergo apoptosis, which is consistent with the findings of other studies (23,24). However, the mechanisms of apoptosis are quite complex and are controlled by various pathways and signals (25).…”
Section: Discussionsupporting
confidence: 81%
“…When human SelM was overexpressed in a transgenic rat model, the animal had lower concentrations of H 2O2, higher SOD and GPX activities, and a higher neutrophil-to-lymphocyte ratio. While suggesting a role for SelM in redox balance, this result provided little insight into the specific functions of endogenous SelM (Hwang et al, 2008).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, in the absence of oxidative challenge, SelM knock-down resulted in decreased cell viability and increased ROS, further demonstrating the functional importance of SelM in preventing oxidative stress. In addition, a recent study reported that overexpression of SelM in a transgenic rat model resulted in the differential regulation of antioxidants as well as the activities of antioxidant enzymes (22).…”
Section: Discussionmentioning
confidence: 99%